New insights into the biennial-to-multidecadal variability of the water level fluctuation in Lake Titicaca in the 20th century - Sulca, Juan; Apaéstegui, James; Tacza, José (Frontiers in Climate, 2024)
The climatological characteristics of the high-and low-frequency components of water level in Lake Titicaca (LTWL) are still not understood. The fluctuations of LTWL during the 1921-2018 period are investigated using continuous wavelet techniques on high and low pass filtered of monthly time series, ERA-20C reanalysis, sea surface temperature (SST) and water level. We also built multiple linear regression (MLR) models based on SST indices to identify the main drivers of the LTWL variability. LTWL features annual (12 months), biennial (22-28 months), interannual (80-108 months), decadal (12.75-14.06 years), interdecadal (24.83-26.50 years), and multidecadal (30-65 years) signals. The high-and low-frequency components of the LTWL are triggered by the humidity transport from the lowland toward the Lake Titicaca basin, although different forcings could cause it. The biennial band is associated with SST anomalies over southeastern tropical Atlantic Ocean that strengthen the Bolivian High-Nordeste Low system. The interannual band is associated with the southern South Atlantic SST anomalies, which modulate the position of the Bolivian High. According to the MLR models, the decadal and interdecadal components of the LTWL can be explained by the linear combination of the decadal and interdecadal variability of the Pacific and Atlantic SST anomalies (r > 0.83, p < 0.05). In contrast, the multidecadal component of the LTWL is driven by the multidecadal component of the North Atlantic SST anomalies (AMO) and the southern South Atlantic SST anomalies. Moreover, the monthly time series of LTWL exhibits four breakpoints. The signs of the first four trends follow the change of phases of the multidecadal component of LTWL, while the fifth trend is zero attributable to the diminished amplitude of the interdecadal component of LTWL. The new outcomes would improve forecasts for managing water resources, including operations for short-and long-term planning of reservoirs, domestic water resources and irrigation sectors.